2020
DOI: 10.1136/bcr-2020-236922
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute hepatitis E infection presenting with acute abdomen and meningoencephalitis

Abstract: We present a case of a 50-year-old man admitted due to acute abdomen, icterus and fever. The patient had a history of sufficiently treated type 2 diabetes and a high daily alcohol consumption, no recent travel history and had a strictly heterosexual and monogamous way of living. A full blood count displayed severe elevated liver enzymes. A CT of the abdomen was performed and revealed steatosis but no acute abdominal pathology. During admission, the patient developed signs of meningoencephalitis. A lumbar punct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Wenter et al reported the case of a 78-year-old immunocompetent diabetes patient, who presented with symptomatic infection by a genotype 3 virus and progressed to acute liver insufficiency [ 8 ]. Ribavirin treatment rapidly lowered the HEV RNA load and led to complete resolution of acute fulminant hepatitis E. Gynthersen et al reported the case of a 50-year-old type 2 diabetic, alcoholic patient admitted for jaundice, fever, and a painful abdomen and who developed meningoencephalitis symptoms [ 9 ]. This patient gradually improved clinically within 8 days post-hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Wenter et al reported the case of a 78-year-old immunocompetent diabetes patient, who presented with symptomatic infection by a genotype 3 virus and progressed to acute liver insufficiency [ 8 ]. Ribavirin treatment rapidly lowered the HEV RNA load and led to complete resolution of acute fulminant hepatitis E. Gynthersen et al reported the case of a 50-year-old type 2 diabetic, alcoholic patient admitted for jaundice, fever, and a painful abdomen and who developed meningoencephalitis symptoms [ 9 ]. This patient gradually improved clinically within 8 days post-hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have documented severe cases of hepatitis E in individuals with diabetes mellitus. [236][237][238][239] Consequently, clinicians should exercise caution to prevent progression to severe liver disease among patients with both HEV infection and diabetes mellitus.…”
Section: Existence Of Metabolic Diseasementioning
confidence: 99%
“…Meningoencephalitis has been described in a few patients [41,43,[64][65][66] but HEV RNA was not always detected in their CSF. One patient was diagnosed by metagenomics next-generation sequencing following CSF analysis.…”
Section: Other Neurological Manifestationsmentioning
confidence: 99%